The LCP Family Protein, Psr, Is Required for Cell Wall Integrity and Virulence in Streptococcus agalactiae - Atefeh Rajaei; Hannah M. Rowe; Melody N. Neely (Microorganisms, 2022)
A robust cell envelope is the first line of protection for an infecting pathogen when encountering the immune defense of its host. In Gram-positive organisms, LytR-CpsA-Psr (LCP) family proteins play a major role in the synthesis and assembly of the cell envelope. While these proteins could be considered for potential new drug targets, not enough is known about how they function to support the integrity of the cell wall. Streptococcus agalactiae (group B streptococcus or GBS) is known to encode at least three LCP family proteins, including CpsA, LytR (BrpA) and Psr. Using strains of GBS that have mutations in two of the three LCP proteins, we were able to determine a role for these proteins in GBS cell wall integrity. The results presented here demonstrate that the absence of Psr results in a decreased growth rate, decreased viability over time, inconsistent cocci morphology and diminished cell wall integrity, as well as an increased penicillin susceptibility, decreased capsule levels and attenuation in virulence in a zebrafish model of infectious disease. A strain that is missing two of the LCP family proteins, CpsA and Psr, exhibits an increase in these defective phenotypes, indicating that CpsA and Psr are partially redundant in function.